2020
DOI: 10.1021/acsomega.0c04499
|View full text |Cite
|
Sign up to set email alerts
|

Modified Group Contribution Scheme to Predict the Glass-Transition Temperature of Homopolymers through a Limiting Property Dataset

Abstract: Previous studies on glass-transition temperature (T g ) prediction mainly focus on developing diverse methods with higher regression accuracy, but very little attention has been paid to the dataset. Generally, a large range of T g values of a specified polymer could be found in the literature but which one should be selected into a dataset merely depends on the implicit preference rather than a recognized and clear criterion. In this paper, limiting glass-transition temperature (T g (∞)), a constant value obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…It is worth mentioning that polymers with side chains are also attractive targets in recent machine learning studies aiming at making accurate predictions of T g of polymers. 33,34 The present work utilizes the GET and molecular dynamics (MD) simulation to investigate the influence of side-chain length and the relative rigidities of the backbone and side chains on the glass formation of branched polymers with a fixed molecular mass. In particular, we study the crossover from linear polymers to comb polymers with side chains of moderate length to bottlebrush polymers, where the side chains can dominate the properties of the polymer material.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is worth mentioning that polymers with side chains are also attractive targets in recent machine learning studies aiming at making accurate predictions of T g of polymers. 33,34 The present work utilizes the GET and molecular dynamics (MD) simulation to investigate the influence of side-chain length and the relative rigidities of the backbone and side chains on the glass formation of branched polymers with a fixed molecular mass. In particular, we study the crossover from linear polymers to comb polymers with side chains of moderate length to bottlebrush polymers, where the side chains can dominate the properties of the polymer material.…”
Section: Introductionsupporting
confidence: 52%
“…These interesting experimental observations, in conjunction with the practical importance of bottlebrush polymers, naturally invite attempts at a theoretical explanation and require simulation to better understand the glass formation of branched polymers at the molecular scale. It is worth mentioning that polymers with side chains are also attractive targets in recent machine learning studies aiming at making accurate predictions of T g of polymers. , …”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that when the average molecular weight is really high, some bulk properties will reach their asymptotic value (The trend can be found in eq ). As molecular weight distribution is the main factor that influences properties, for these properties, it is suggested to use the limiting value instead of the original property value: where f ( X (∞)) is the function of certain limiting property X (∞), and C i (∞) is the limiting contribution of the i group, which occurs N i times. In this work, eq is used to calculate glass transition temperature and surface tension.…”
Section: Improved Computer-aided Polymer Design Methodologymentioning
confidence: 99%
“…The results are shown in Table 2 and Figure 2. The contribution of groups for glass transition temperature and surface tension can be found in a previous work 32 and Table S1 in the Supporting Information, respectively.…”
Section: Improved Computer-aided Polymer Designmentioning
confidence: 99%
“…It was found that the predicted result was very close to the experimental data. Yang et al 12 established a new data set containing 198 polymers to predict Tg ∞ (Tg of limit degree of polymerization (DP)) using the improved GC method which showed a good correlation. Karteek et al 13 created the density functional theory (DFT) forcefield and improved the traditional polymer consistent force field (PCFF) to obtain a wider applicable modified PCFF (m-PCFF), and the Tg values for Calculation of the glass transition temperature (Tg) from different methods of poly-(p-phenylenediamine-alt-2,6-diformyl tetraphenyl) (PPDM-4) a number of yet-to-be-synthesized polyhydroxyalkanoates (PHA)-based polymers with a diverse set of functional groups on the polymer side chains were predicted by using this forcefield.…”
Section: Introductionmentioning
confidence: 99%